Pengaruh Edukasi Pencegahan Stroke terhadap Pengetahuan pada Lansia di Gereja Isa Al-Masih Kota Kediri: The Effect of Stroke Prevention Education on Knowledge of Elderly at the Church of Isa Al-Masih, Kediri City - Maharani H, Claudy; Widiastutik, Cornelia; Ayu W, Debora Aurelia; Nugraha, Jonathan Adjie; Ambu K, Maria Aldanita; Devinda P.M, Putri; Puspita, Nanda; Suwardianto, Heru (Chakra Brahmanda Lentera Institute, 2026)
Stroke is one of the leading causes of disability and mortality among the elderly. Preventive efforts focusing on increasing knowledge and awareness are essential to reduce stroke risk and improve quality of life. This study used a pre–post-test design with 62 elderly participants who regularly attended the Church Isa Al-Masih in Kediri City. The intervention consisted of stroke prevention education delivered through a standardized procedure (SOP) using leaflets and flipbooks. Knowledge was assessed with a 6-item questionnaire covering hypertension, causes of high blood pressure, normal blood pressure ranges, medication adherence, diet, and breathing relaxation techniques. Data were collected before and after the education and analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test. The Wilcoxon test indicated a significant increase in participants’ knowledge following the stroke prevention education (p < 0.05). Structured, interactive, and community-based education enhanced understanding of stroke risk factors, blood pressure management, medication adherence, diet, and relaxation techniques. Stroke prevention education is effective in enhancing knowledge among elderly individuals and may encourage preventive health behaviors. Community-based approaches can serve as a model for similar health promotion programs targeting older adults.